The effect of low-dose oral vitamin K supplementation on INR stability in patients receiving warfarin - Boonyawat, Kochawan; Wang, Luqi; Lazo-Langner, Alejandro; Kovacs, Michael J.; Yeo, Erik; Schnurr, Terri; Schulman, Sam; Crowther, Mark A. (Thrombosis and Haemostasis, 2016)
The anticoagulant effect of warfarin is influenced by variations in vitamin K intake. Concomitant use of daily low-dose oral vitamin K (LDVK) and warfarin may improve INR stability. We hypothesise that administration of LDVK improves INR control. To test this hypothesis we performed a multi-centre, placebo-controlled, randomised trial conducted at four university-affiliated hospitals in Canada. Patients on chronic warfarin therapy received oral vitamin K 150 mcg daily or a matching placebo for a total of six months after a one-month run in period. The primary outcome was a comparison of mean time in therapeutic range (TTR) in LDVK and placebo group during a six-month-period. The secondary outcome was number of INR excursions <1.5 or >4.5. There was no significant difference in the final TTR between the two groups (65.1 % vs 66 %, p =0.8). Mean TTR in both LDVK and placebo groups were statistically increased compared with prior to the study. The number of INR excursions were significantly decreased in the LDVK group (9.4 % and 5.4 %, absolute difference [pre- minus post-] = 4 %, 95 % CI, 2 to 6 %, p-value <0.001). We conclude that LDVK administration did not increase mean TTR, but did decrease the number of INR excursions. The observed improvement in mean TTR in both groups suggests that more attentive monitoring of warfarin therapy, rather than LDVK, was responsible for the improvement in TTR observed. The reduced excursions suggest that LDVK did reduce extreme INR variation. The study is registered at www.ClinicalTrial.gov#NCT00990158.
Keywords: Administration; oral; clinical trial; international normalised ratio; vitamin K; warfarin